Interaksi Simbolik Dalam Upacara Sengkure Di Kabupaten Kaur - Wike Selvia Pauzi; Hafri Yuliani; Bintara Santika Putra (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the meaning of the Sengkure Ceremony, an annual tradition of the Nasal tribe in Kaur Regency, Bengkulu, which is rich in symbolic meaning and social value. This study uses Herbert Blumer's symbolic interaction theory. The method used is qualitative with a case study design, through participatory observation, in-depth interviews, and documentation. The results of the study show that Blumer's three premises of action are based on meaning. The first premise is that meaning arises from social interaction, with symbols such as ijuk costumes, pandan masks, the Eid al-Fitr holiday, and the journey to the Nasal River representing spiritual transformation and self-purification. The second premise is that a process of interaction occurs in which symbols and beliefs come together in an event. The third premise is that these meanings are passed down through folklore and cross-generational social practices, and adapted in a modern context through cultural festivals and digital media.